2021
DOI: 10.1128/jvi.01227-21
|View full text |Cite
|
Sign up to set email alerts
|

Nectin-1 Is an Entry Mediator for Varicella-Zoster Virus Infection of Human Neurons

Abstract: Varicella zoster virus (VZV) maintains lifelong latency in neurons following initial infection and can subsequently be reactivated to result in herpes zoster or severe neurological manifestations such as encephalitis. Mechanisms of VZV neuropathogenesis have been challenging to study due to the strict human tropism of the virus. While neuronal entry mediators of other herpesviruses, including herpes simplex virus, have been identified, little is known regarding how VZV enters neurons. Here, we utilize a human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…VZV has been detected in dorsal root ganglia, cranial nerve ganglia, and various autonomic ganglia in the enteric nervous system, and in astrocytes. Nectin-1, which is highly expressed in neurons, seems to be involved in viral entry of axons and cell bodies [7].…”
Section: Etiologymentioning
confidence: 99%
“…VZV has been detected in dorsal root ganglia, cranial nerve ganglia, and various autonomic ganglia in the enteric nervous system, and in astrocytes. Nectin-1, which is highly expressed in neurons, seems to be involved in viral entry of axons and cell bodies [7].…”
Section: Etiologymentioning
confidence: 99%
“…There is no significant difference between F129A and 135 KO in the resistances against intranasal infection with higher dose of PRV (50 LD 50 ) ( P =0.789). Phenylalanine 129 of nectin-1 V-domain is most important as interfacing to the gD of alphaherpesvirus including PRV in vitro [ 8 , 17 , 27 ]. In particular, it has been indicated that mutation of F129A inhibits nectin-1 binding to gD and viral entry [ 8 , 17 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phenylalanine 129 of nectin-1 V-domain is most important as interfacing to the gD of alphaherpesvirus including PRV in vitro [ 8 , 17 , 27 ]. In particular, it has been indicated that mutation of F129A inhibits nectin-1 binding to gD and viral entry [ 8 , 17 , 27 ]. Our present results seen with F129A nectin-1 mouse strongly support the results provided by these in vitro experiments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations